Reef Fish Diversity in Jayapura City, Indonesia: A Preliminary Study - Baigo Hamuna; Lisiard Dimara; Alianto Alianto (Journal of Tropical Biodiversity and Biotechnology, 2022)
As one of the marine areas included in the world's Coral Triangle region, Yos Sudarso Bay have a potential reef fish diversity that needs to be studied. However, there is very little information about reef fish diversity in these waters to date. This study aims to determine the species diversity of reef fish in Yos Sudarso Bay, Jayapura City, Indonesia. The study was conducted in April 2020 at seven sites; six of them located inside the Yos Sudarso Bay and one more located outside the bay. Sampling was carried out using the Underwater Visual Census method (25 m long and 5 m wide). Relative abundance by species, and diversity (H´), evenness (E), and dominance (C) indices were calculated. A total of 1,075 individual reef fish was recorded in seven study sites, representing 122 species and 26 families. Locations showed differences in reef fish abundance (86 to 215 individuals/125 m2), diversity (H´= 2.462 to 3.358), evenness (E = 0.770 to 0.887), and dominance (C = 0.047 to 0.155). This study has provided preliminary information on species diversity, fish abundance, and the ecological index of reef fish in Yos Sudarso Bay, Jayapura City.